2004
DOI: 10.1063/1.1688450
|View full text |Cite
|
Sign up to set email alerts
|

Systematic design of photonic crystal structures using topology optimization: Low-loss waveguide bends

Abstract: Topology optimization is a promising method for systematic design of optical devices. As an example, we demonstrate how the method can be used to design a 90° bend in a two-dimensional photonic crystal waveguide with a transmission loss of less than 0.3% in almost the entire frequency range of the guided mode. The method can directly be applied to the design of other optical devices, e.g., multiplexers and wave splitters, with optimized performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
166
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 256 publications
(168 citation statements)
references
References 11 publications
2
166
0
Order By: Relevance
“…Recently, the topology optimization method has been applied to the design of wave-propagation problems based on band gap structures both for phononic and photonic applications (Sigmund and Jensen, 2003;Jensen and Sigmund, 2004). A special feature of these problems is that they require no volume constraint.…”
Section: The Wave Transmittermentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the topology optimization method has been applied to the design of wave-propagation problems based on band gap structures both for phononic and photonic applications (Sigmund and Jensen, 2003;Jensen and Sigmund, 2004). A special feature of these problems is that they require no volume constraint.…”
Section: The Wave Transmittermentioning
confidence: 99%
“…Usually, the post-processed structure has a performance that is very close to the optimized structure. However, recently the author's research group has applied the topology optimization to phononic and photonic crystal design (Sigmund and Jensen, 2003;Jensen and Sigmund, 2004) where structures with intricate semi-periodic patterns appear as the result of the topology optimization process. An example of the design of a nano-scale optical splitter from Borel et al (2005) is shown in Fig.1b.…”
Section: Introductionmentioning
confidence: 99%
“…The material distribution method in topology optimization was originally developed for stiffness design of mechanical structures [2] but has now been extended to a multitude of design problems in structural mechanics as well as to optics and acoustics [3,4,5,6]. Recently Borrvall and Petersson introduced the method for fluids in Stokes flow [1].…”
Section: Introductionmentioning
confidence: 99%
“…Topology optimization [4] has previously been utilized to optimize the performance of different photonic crystal waveguide components [5,6]. Here, we apply this inverse design method to design a compact, broadband and low-loss photonic wire splitter.…”
Section: Introductionmentioning
confidence: 99%